Outcomes of Patients with Multiple Myeloma in Middle Euphrates Region of Iraq: Data from Developing Country - Mjali, Ahmed; Jawad, Safaa Ayad; Abbas, Nareen Tawfeeq (Asian Pacific Journal of Cancer Biology, 2021)
Background: Multiple myeloma (MM) is a B cells neoplasm characterized by plasma cells clonal proliferation. Aims: The aim of this study was to evaluate incidence, prevalence and pattern of multiple myeloma (MM) in Middle Euphrates region of Iraq. Materials and Methods: A retrospective descriptive conducted at Al-Hussein center in Karbala province of Iraq between February 2012 and February 2020. Results: A total of 78 patients with MM were included in this study, median age at presentation was 59.8 years, M:F ratio was 0.85:1. The most frequent presenting complain was bony lesions in 87.18% of patients, IgG was the most frequent paraprotient in 61.53% and VRD was the most common used protocol in 37.18% . Survival rate was higher in younger & female patients, while there was no correlation between myeloma defining events and early death in our study. Conclusion: MM presenting age in our region was close to other parts of Iraq and neighboring countries but younger than western countries with female predominance. Giving that the majority of the patients presented with advance stage disease, therefore raising awareness of early symptoms is recommended for early diagnosis and proper management.